Carpobrotus taxa benefit more from clonal integration in their non-native than native ranges - Marta Pérez-Diz; Hana Skálová; Susan Canavan; María Loreto Castillo; Paula Gervazoni; Luís González; Petr Pyšek; Jonatan Rodríguez; Kateřina Štajerová; Giuseppe Brundu; Carla M. D’Antonio; Tom Dudley; et al. (Biological Invasions, 2026)
Understanding physiological integration in invasive clonal plants is relevant to invasion biology because resource transfer across ramets may allow alien plants to buffer spatial heterogeneity in their introduced areas. However, experimental evidence across native and non-native ranges is limited. Here, we tested whether physiological integration provides greater performance benefits to Carpobrotus taxa in non-native than native ranges. We grew clonal fragments under controlled conditions from eleven populations representing different genetic clusters across their native and non-native ranges. Connected recipient ramets showed higher growth than severed ones, with increased ramet length, node number, Branching and Vigor Indices, while connected donor ramets showed reduced growth, indicating resource redistribution within the clone. Plants from non-native ranges exhibited overall higher growth-related traits and chlorophyll content, suggesting enhanced growth and stress tolerance across genetic backgrounds. These results indicate that physiological integration allows Carpobrotus taxa to overcome environmental heterogeneity by reallocating resources among ramets, promoting clonal growth and expansion, and potentially increasing competitive ability in non-native ranges. Our findings provide experimental evidence across multiple populations that physiological integration can promote the ecological success of clonal invaders.